2011
DOI: 10.1111/j.1743-498x.2011.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative assessment clinic: a missed learning opportunity?

Abstract: The results clearly demonstrate that preoperative assessment is an arena that would give medical students two important opportunities: to examine objective clinical signs and to take histories of presenting complaints from the core curriculum. This learning opportunity would otherwise be missed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that students enjoy learning in the preoperative assessment clinic, and that it presents the opportunity to take histories and examine patients with clinical signs 5,8 . This study shows that students can also gain experience in other Tomorrow’s Doctors outcomes, which form the basis for UK medical school curricula.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Previous studies have shown that students enjoy learning in the preoperative assessment clinic, and that it presents the opportunity to take histories and examine patients with clinical signs 5,8 . This study shows that students can also gain experience in other Tomorrow’s Doctors outcomes, which form the basis for UK medical school curricula.…”
Section: Discussionmentioning
confidence: 67%
“…6 The experience of our students appears consistent with the findings of Bagenal et al: the majority of patients have presenting complaints and clinical signs relevant to our core curriculum, and represent a valuable and willing educational resource. 5 However, the potential of the preoperative assessment clinic extends beyond exposure to pathology, and this is of particular relevance as students approach graduation and must achieve competence in clinical reasoning, teamwork and communication, as stated in Tomorrow's Doctors. 7 In September 2011, a new preoperative assessment teaching programme was introduced for fourth-year medical students, who attend the general surgical preoperative assessment clinic for three half-day sessions during their surgical attachment.…”
Section: Students Can Gain Experience In Multiplementioning
confidence: 88%
See 2 more Smart Citations
“…We were interested to read Bagenal et al. ’s paper indicating that the preoperative assessment area is suitable for teaching medical students 1 …”
mentioning
confidence: 99%